Alloy composite material of circuit board shielding case as well as preparation method and application of alloy composite material
By using a multi-layered structure and cold rolling process to composite circuit board shielding material, the problems of bending deformation and uneven welding due to differences in melting points caused by heat conduction of thin plates are solved, resulting in a circuit board shielding material with high precision, stability and high conductivity.
Patent Information
- Application Number
- CN202411571728.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing circuit board shielding materials are prone to bending and deformation due to the high thermal conductivity of thin plates, and the difference in melting points leads to uneven welding, affecting product precision and stability.
It adopts a multi-layer structure, including a first stainless steel layer, an alloy transition layer, a T2 copper layer, and a second stainless steel layer, which are tightly bonded together through a cold rolling process. An appropriate amount of silicon nitride is added to enhance antimagnetic properties and corrosion resistance.
It improves the geometric accuracy and structural stability of the material, enhances welding strength and conductivity, extends service life, and reduces the temperature sensitivity of conductivity under high-temperature conditions.
Smart Images

Figure BDA0005120627370000121 
Figure BDA0005120627370000122 
Figure BDA0005120627370000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of circuit board shielding covers, and in particular to an alloy composite material of a circuit board shielding cover and a preparation method and application thereof. Background Art
[0002] Copper is a good electromagnetic shielding material with high conductivity and can effectively provide shielding performance. In circuit board design, shielding cans are often used to isolate sensitive circuits to prevent them from being affected by electromagnetic interference or interfering with other circuits. The material selection of shielding cans usually includes nickel silver, stainless steel, and tinplate. The corrosion resistance and mechanical strength of stainless steel make it more durable than copper, but copper is generally better than stainless steel in electromagnetic shielding performance.
[0003] For example, Chinese patent CN212573096U discloses a circuit board shielding cover that is easy to replace, including a first nickel silver sheet and a positioning bracket, support steel feet are arranged on the left and right sides of the first nickel silver sheet, and stress holes are penetrated through the outer sides of the support steel feet, bolt holes are penetrated through the outer sides of the support steel feet, screw holes are penetrated through the outer sides of the first nickel silver sheet, and first alloy patches are welded and fixed on the left and right sides of the first nickel silver sheet, the positioning bracket is welded to the outer side of the first nickel silver sheet, and a second nickel silver sheet is clamped and connected between the positioning brackets, a stainless steel sheet is welded and fixed to the bottom of the first nickel silver sheet, and a guide rail is welded and fixed to the outer side of the stainless steel sheet.
[0004] Although the above patent provides anti-magnetic properties through nickel silver and stainless steel increases corrosion resistance and mechanical strength, since the nickel silver and stainless steel sheets are thin, the heat conduction rate of the thin plates is fast, which may cause bending deformation and affect the accuracy and stability of the final product; in addition, due to the large difference in melting points between nickel silver and stainless steel, it may cause uneven welding and reduce the strength of the welded joint.
[0005] Based on this, the present invention designs an alloy composite material of a circuit board shielding cover and a preparation method and application thereof to solve the above problems. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides an alloy composite material for a circuit board shielding cover and a preparation method and application thereof.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0008] The alloy composite material of the circuit board shielding cover comprises a first stainless steel layer, a T2 copper layer and a second stainless steel layer in sequence;
[0009] Wherein, an alloy transition layer is provided between the first stainless steel layer and the T2 copper layer, and between the second stainless steel layer and the T2 copper layer;
[0010] The alloy transition layer includes the following components: nickel: 2.2%-2.6%, chromium: 4.5%-5.8%, sulfur ≤0.4%, silicon nitride: 0.2%-0.6%, and the rest is copper and inevitable impurities.
[0011] The method for preparing the circuit board shielding cover alloy composite material comprises the following steps:
[0012] Step 1: weigh raw materials according to the ratio of nickel: 2.2%-2.6%, chromium: 4.5%-5.8%, sulfur ≤0.4%, silicon nitride: 0.2%-0.6%, and the balance is copper, melt the raw materials into a melt, deoxidize the melt in turn, cast it into an ingot, and roll it to obtain an alloy transition layer;
[0013] Step 2: Compounding the front and back sides of the pickled and roughened T2 copper layer with the alloy transition layer through a cold rolling process to obtain a preliminary composite material;
[0014] The reduction rate is 4-8%, the rolling force is 7-9MN, and the rolling speed is 2-4m / min.
[0015] Step 3: Compounding the first stainless steel layer and the second stainless steel layer after pickling and roughening treatment on the front and back sides of the preliminary composite material by cold rolling process, thereby obtaining an alloy composite material of the circuit board shielding cover;
[0016] The reduction rate is 4-8%, the rolling force is 7-9MN, and the rolling speed is 2-4m / min.
[0017] Preferably, the T2 copper layer has a thickness of 0.1-0.12 mm.
[0018] Preferably, the thickness of the first stainless steel layer and the second stainless steel layer is 0.03-0.05 mm.
[0019] Preferably, the thickness of the transition layer is 0.01-0.05 mm.
[0020] Preferably, the first stainless steel layer and the second stainless steel layer are made of 304 stainless steel or 316 stainless steel.
[0021] The alloy composite material of the circuit board shielding cover is used in preparing the circuit board shielding cover.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. In the process of manufacturing alloy composite materials, the present invention cleverly uses the cold rolling process to tightly and evenly compound the carefully designed multi-layer structure, namely the first stainless steel layer, the alloy transition layer, the high-quality T2 copper layer, the alloy transition layer and the second stainless steel layer. This process not only effectively overcomes the bending deformation problem that may be caused by the high thermal conductivity rate of the thin plate material, thereby ensuring that the geometric accuracy and structural stability of the final product reach the optimal state; at the same time, it also cleverly avoids the welding challenges caused by the difference in melting points of the various layers of materials, significantly reduces the uneven phenomenon in the welding process, and thus greatly improves the connection strength between materials and the reliability of the overall structure.
[0024] 2. The present invention cleverly combines stainless steel and high-quality T2 copper materials through carefully designed composite technology, which not only enhances the anti-magnetic properties of the material, making it exhibit excellent stability and reliability in an electromagnetic interference environment, but also significantly improves the overall conductivity efficiency, bringing more efficient and stable solutions for applications in the fields of power transmission, signal conduction, etc.
[0025] 3. The introduction of stainless steel components in the present invention not only provides the composite material with corrosion-resistant "armor", effectively resisting the erosion of various corrosive media and extending the service life of the product, but also greatly enhances the mechanical strength of the material, enabling it to maintain structural integrity and stability in a complex and changeable working environment, showing excellent durability.
[0026] 4. Aiming at the pain point that the conductive properties of traditional conductive materials are easily damaged in high temperature environments, the present invention introduces an appropriate amount of silicon nitride as a key additive. Without the addition of silicon nitride, the conductivity tends to show a linear downward trend with the increase in temperature, affecting the use effect of the material under high temperature conditions. The present invention successfully constructs a "temperature barrier" by cleverly adding an appropriate amount of silicon nitride, which significantly weakens the negative impact of temperature on the resistivity of the material and effectively curbs the attenuation of conductive properties caused by rising temperature. It is worth mentioning that when the ambient temperature rises to 40°C or above 40°C, the adverse effect of this temperature on conductivity is further weakened, effectively reducing the temperature sensitivity of conductive properties, providing strong support for applications in high temperature environments. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Embodiment 1
[0029] This embodiment provides a method for preparing a circuit board shielding cover, wherein the circuit board shielding cover sequentially comprises a first stainless steel layer, a T2 copper layer and a second stainless steel layer;
[0030] Wherein, an alloy transition layer is provided between the first stainless steel layer and the T2 copper layer, and between the second stainless steel layer and the T2 copper layer;
[0031] The first stainless steel layer and the second stainless steel layer are made of 304 stainless steel;
[0032] The first stainless steel layer and the second stainless steel layer are made of 316 stainless steel;
[0033] Step 1: weighing raw materials, nickel powder, chromium powder, sulfur powder, silicon nitride powder and copper powder in proportion, smelting the raw materials into a melt, deoxidizing and casting the melt into an ingot in turn, and rolling to obtain an alloy transition layer;
[0034] Step 2: Compounding the front and back sides of the pickled and roughened T2 copper layer with the alloy transition layer through a cold rolling process to obtain a preliminary composite material;
[0035] Rolling speed 4m / min, reduction rate 8%, rolling force 9MN, pressure 30MPa;
[0036] Step 3: Compounding the pickled and roughened first stainless steel layer and the second stainless steel layer on the front and back sides of the preliminary composite material respectively by cold rolling process, and heat preservation at 500° C. for 8 hours to obtain the alloy composite material of the circuit board shielding cover; the thickness of the T2 copper layer is 0.12 mm;
[0037] The thickness of the first stainless steel layer and the second stainless steel layer is 0.05 mm;
[0038] The thickness of the transition layer is 0.05 mm;
[0039] Rolling speed 4m / min, reduction rate 8%, rolling force 9MN, pressure 30MPa;
[0040] Step 4: Cutting and stamping to obtain the circuit board shielding cover.
[0041] The alloy transition layer includes the following components: nickel: 2.2%-2.6%, chromium: 4.5%-5.8%, sulfur ≤0.4%, silicon nitride: 0.2%-0.6%, and the rest is copper and inevitable impurities.
[0042] 316 stainless steel is a low-sulfur austenitic stainless steel. It contains a low sulfur content, which makes it less prone to intergranular corrosion during welding, so no annealing is required after welding, which makes it very popular in some welding applications. The thermal conductivity of 316 stainless steel is about 16.3W / (m·K) at 100°C and about 21.5W / (m·K) at 500°C. In the present invention, the thermal conductivity of the three-layer structure is affected by the thermal conductivity of each layer of material and their thickness ratio because it is a composite structure composed of different materials.
[0043] T2 copper (pure copper) is a widely used conductive and thermal conductive material. The thermal conductivity of T2 copper at room temperature is about 401W / (m·K). It can still maintain good thermal conductivity at 100 degrees Celsius, and the thermal conductivity at 100 degrees Celsius is about 380W / (m·K). This means that even at a temperature of 100 degrees Celsius, T2 copper can still conduct heat effectively.
[0044] In addition, the recrystallization temperature of T2 copper is between 200 and 280 degrees Celsius, indicating that it can still maintain good physical properties in this temperature range. At 100 degrees Celsius, T2 copper will not significantly affect its heat conduction performance due to temperature increase.
[0045] The thermal conductivity of stainless steel is relatively low, while the thermal conductivity of T2 copper is relatively high. In the multilayer structure of the present invention, heat is mainly conducted through the copper layer, so the overall thermal conductivity is between stainless steel and copper, but because the thermal conductivity of copper is much higher than that of stainless steel, the thermal conductivity is closer to that of copper.
[0046] T2 copper is a high-purity copper material with good electrical conductivity, thermal conductivity and machinability. It is widely used in electronics, electrical appliances, construction, aerospace and other fields. Its main chemical components include: copper (Cu) + silver (Ag) ≥ 99.9%, lead (Pb) ≤ 0.005%, iron (Fe) ≤ 0.005%, arsenic (As) ≤ 0.002%, antimony (Sb) ≤ 0.002%, sulfur (S) ≤ 0.005%. The density is about 8.96g / cm 3 , melting point is about 1083℃, linear expansion coefficient is about 16.6×10^(-6) / ℃. The tensile strength (Rm / MPa) of T2 copper is ≥295, Rockwell hardness (HRF) is ≥65, and elongation (%) is ≥3. The manufacturing process of T2 copper includes smelting, casting, forging and heat treatment. It is widely used in industries such as electricity, electronics, machinery manufacturing and chemical industry.
[0047] 304 stainless steel is a common austenitic stainless steel with good corrosion resistance and formability. Its chemical composition is as follows: sulfur (C) ≤ 0.08%, silicon (Si) ≤ 1.00%, manganese (Mn) ≤ 2.00%, phosphorus (P) ≤ 0.045%, sulfur (S) ≤ 0.030%, chromium (Cr) 18.00%-20.00%, nickel (Ni) 8.00%-11.00%. The chromium and nickel content in 304 stainless steel is high, which enables it to form a dense chromium oxide film in an oxidizing environment, thereby providing good corrosion resistance. This stainless steel is widely used in household goods, automotive accessories, medical equipment, building materials, chemical and food industries.
[0048] 316 stainless steel is a kind of austenitic stainless steel containing molybdenum, which has better corrosion resistance than 304 stainless steel, especially in the environment containing chloride ions. Its chemical composition is as follows: sulfur (C) ≤ 0.08%, silicon (Si) ≤ 1.00%, manganese (Mn) ≤ 2.00%, phosphorus (P) ≤ 0.045%, sulfur (S) ≤ 0.030%, chromium (Cr) 16.00% -18.00%, nickel (Ni) 10.00% -14.00%, molybdenum (Mo) 2.00% ~ 3.00%. These ingredients make 316 stainless steel widely used in chemical industry, marine environment, papermaking and food processing industries.
[0049] The circuit board shielding cover prepared by the invention meets the following standards: hardness (HV) 250-270; tensile strength (Mpa) 520-570; yield strength (Mpa) 470-500; thermal conductivity of about 380W / (m·K).
[0050] Embodiment 2
[0051] This embodiment provides a method for preparing a circuit board shielding cover, wherein the circuit board shielding cover sequentially comprises a first stainless steel layer, a T2 copper layer and a second stainless steel layer;
[0052] Wherein, an alloy transition layer is provided between the first stainless steel layer and the T2 copper layer, and between the second stainless steel layer and the T2 copper layer;
[0053] The first stainless steel layer and the second stainless steel layer are made of 316 stainless steel;
[0054] The first stainless steel layer and the second stainless steel layer are made of 316 stainless steel;
[0055] The copper content of the T2 copper layer is ≥ 2%;
[0056] Step 1: weighing raw materials, nickel powder, chromium powder, sulfur powder, silicon nitride powder and copper powder in proportion, smelting the raw materials into a melt, deoxidizing and casting the melt into an ingot in turn, and rolling to obtain an alloy transition layer;
[0057] Step 2: Compounding the front and back sides of the pickled and roughened T2 copper layer with the alloy transition layer through a cold rolling process to obtain a preliminary composite material;
[0058] The rolling speed is 2m / min, the reduction rate is 4%, the rolling force is 7MN, and the pressure is 30MPa;
[0059] Step 3: Compounding the pickled and roughened first stainless steel layer and the second stainless steel layer on the front and back sides of the preliminary composite material respectively by cold rolling process, and heat preservation at 500° C. for 8 hours to obtain the alloy composite material of the circuit board shielding cover; the thickness of the T2 copper layer is 0.1 mm;
[0060] The thickness of the first stainless steel layer and the second stainless steel layer is 0.03 mm;
[0061] The thickness of the transition layer is 0.01 mm;
[0062] The rolling speed is 2m / min, the reduction rate is 4%, the rolling force is 7MN, and the pressure is 30MPa;
[0063] Step 4: Cutting and stamping to obtain the circuit board shielding cover.
[0064] The alloy transition layer includes the following components: nickel: 2.2%-2.6%, chromium: 4.5%-5.8%, sulfur ≤0.4%, silicon nitride: 0.2%-0.6%, and the rest is copper and inevitable impurities.
[0065] Embodiment 3
[0066] This embodiment provides a method for preparing a circuit board shielding cover, wherein the circuit board shielding cover sequentially comprises a first stainless steel layer, a T2 copper layer and a second stainless steel layer;
[0067] Wherein, an alloy transition layer is provided between the first stainless steel layer and the T2 copper layer, and between the second stainless steel layer and the T2 copper layer;
[0068] The first stainless steel layer and the second stainless steel layer are made of 316 stainless steel;
[0069] The first stainless steel layer and the second stainless steel layer are made of 304 stainless steel;
[0070] The copper content of the T2 copper layer is ≥ 2%;
[0071] Step 1: weighing raw materials, nickel powder, chromium powder, sulfur powder, silicon nitride powder and copper powder in proportion, smelting the raw materials into a melt, deoxidizing and casting the melt into an ingot in turn, and rolling to obtain an alloy transition layer;
[0072] Step 2: Compounding the front and back sides of the pickled and roughened T2 copper layer with the alloy transition layer through a cold rolling process to obtain a preliminary composite material;
[0073] Rolling speed 3m / min, reduction rate 5%, rolling force 8MN, pressure 30MPa;
[0074] Step 3: Compounding the pickled and roughened first stainless steel layer and the second stainless steel layer on the front and back sides of the preliminary composite material respectively by cold rolling process, and heat preservation at 500° C. for 8 hours to obtain the alloy composite material of the circuit board shielding cover; the thickness of the T2 copper layer is 0.1 mm;
[0075] The thickness of the first stainless steel layer and the second stainless steel layer is 0.04 mm;
[0076] The thickness of the transition layer is 0.02 mm;
[0077] Rolling speed 3m / min, reduction rate 5%, rolling force 8MN, pressure 30MPa;
[0078] Step 4: Cutting and stamping to obtain the circuit board shielding cover.
[0079] The alloy transition layer includes the following components: nickel: 2.2%-2.6%, chromium: 4.5%-5.8%, sulfur ≤0.4%, silicon nitride: 0.2%-0.6%, and the rest is copper and inevitable impurities.
[0080] Comparative Example 1
[0081] The difference between this comparative example and the third embodiment is that no alloy transition layer is provided between the first stainless steel layer and the T2 copper layer, and between the second stainless steel layer and the T2 copper layer.
[0082] This comparative example provides a method for preparing a circuit board shielding cover, wherein the circuit board shielding cover sequentially comprises a first stainless steel layer, a T2 copper layer, and a second stainless steel layer;
[0083] Wherein, an alloy transition layer is provided between the first stainless steel layer and the T2 copper layer, and between the second stainless steel layer and the T2 copper layer;
[0084] The first stainless steel layer and the second stainless steel layer are made of 316 stainless steel;
[0085] The first stainless steel layer and the second stainless steel layer are made of 304 stainless steel;
[0086] The copper content of the T2 copper layer is ≥ 2%;
[0087] Step 1: Compounding the pickled and roughened first stainless steel layer and the second stainless steel layer on the front and back sides of the T2 copper layer respectively by cold rolling process, and heat preservation at 500° C. for 8 hours to obtain an alloy composite material of the circuit board shielding cover; the thickness of the T2 copper layer is 0.1 mm;
[0088] The thickness of the first stainless steel layer and the second stainless steel layer is 0.04 mm;
[0089] The thickness of the transition layer is 0.02 mm;
[0090] Rolling speed 3m / min, reduction rate 5%, rolling force 8MN, pressure 30MPa;
[0091] Step 2: Cutting and stamping to obtain the circuit board shielding cover.
[0092] Comparative Example 2
[0093] The difference between this comparative example and Example 3 is that the content of silicon nitride is less than 0.2%.
[0094] This embodiment provides a method for preparing a circuit board shielding cover, wherein the circuit board shielding cover sequentially comprises a first stainless steel layer, a T2 copper layer and a second stainless steel layer;
[0095] Wherein, an alloy transition layer is provided between the first stainless steel layer and the T2 copper layer, and between the second stainless steel layer and the T2 copper layer;
[0096] The first stainless steel layer and the second stainless steel layer are made of 316 stainless steel;
[0097] The first stainless steel layer and the second stainless steel layer are made of 304 stainless steel;
[0098] The copper content of the T2 copper layer is ≥ 2%;
[0099] Step 1: weighing raw materials, nickel powder, chromium powder, sulfur powder, silicon nitride powder and copper powder in proportion, smelting the raw materials into a melt, deoxidizing and casting the melt into an ingot in turn, and rolling to obtain an alloy transition layer;
[0100] Step 2: Compounding the front and back sides of the pickled and roughened T2 copper layer with the alloy transition layer through a cold rolling process to obtain a preliminary composite material;
[0101] Rolling speed 3m / min, reduction rate 5%, rolling force 8MN, pressure 30MPa;
[0102] Step 3: Compounding the pickled and roughened first stainless steel layer and the second stainless steel layer on the front and back sides of the preliminary composite material respectively by cold rolling process, and heat preservation at 500° C. for 8 hours to obtain the alloy composite material of the circuit board shielding cover; the thickness of the T2 copper layer is 0.1 mm;
[0103] The thickness of the first stainless steel layer and the second stainless steel layer is 0.04 mm;
[0104] The thickness of the transition layer is 0.02 mm;
[0105] Rolling speed 3m / min, reduction rate 5%, rolling force 8MN, pressure 30MPa;
[0106] Step 4: Cutting and stamping to obtain the circuit board shielding cover.
[0107] The alloy transition layer includes the following components: nickel: 2.2%-2.6%, chromium: 4.5%-5.8%, sulfur ≤0.4%, silicon nitride: 0.05%, and the rest is copper and inevitable impurities.
[0108] Comparative Example 3
[0109] The difference between this comparative example and Example 3 is that the content of silicon nitride is higher than 0.6%.
[0110] This embodiment provides a method for preparing a circuit board shielding cover, wherein the circuit board shielding cover sequentially comprises a first stainless steel layer, a T2 copper layer and a second stainless steel layer;
[0111] Wherein, an alloy transition layer is provided between the first stainless steel layer and the T2 copper layer, and between the second stainless steel layer and the T2 copper layer;
[0112] The first stainless steel layer and the second stainless steel layer are made of 316 stainless steel;
[0113] The first stainless steel layer and the second stainless steel layer are made of 304 stainless steel;
[0114] The copper content of the T2 copper layer is ≥ 2%;
[0115] Step 1: weighing raw materials, nickel powder, chromium powder, sulfur powder, silicon nitride powder and copper powder in proportion, smelting the raw materials into a melt, deoxidizing and casting the melt into an ingot in turn, and rolling to obtain an alloy transition layer;
[0116] Step 2: Compounding the front and back sides of the pickled and roughened T2 copper layer with the alloy transition layer through a cold rolling process to obtain a preliminary composite material;
[0117] Rolling speed 3m / min, reduction rate 5%, rolling force 8MN, pressure 30MPa;
[0118] Step 3: Compounding the pickled and roughened first stainless steel layer and the second stainless steel layer on the front and back sides of the preliminary composite material respectively by cold rolling process, and heat preservation at 500° C. for 8 hours to obtain the alloy composite material of the circuit board shielding cover; the thickness of the T2 copper layer is 0.1 mm;
[0119] The thickness of the first stainless steel layer and the second stainless steel layer is 0.04 mm;
[0120] The thickness of the transition layer is 0.02 mm;
[0121] Rolling speed 3m / min, reduction rate 5%, rolling force 8MN, pressure 30MPa;
[0122] Step 4: Cutting and stamping to obtain the circuit board shielding cover.
[0123] The alloy transition layer includes the following components: nickel: 2.2%-2.6%, chromium: 4.5%-5.8%, sulfur ≤0.4%, silicon nitride: 0.9%, and the rest is copper and inevitable impurities.
[0124] Experimental example
[0125] 1. Magnetic susceptibility detection:
[0126] Make the sample box containing the sample (Φ4×5mm) be located in the linear region, and make the suspension wire pass through the origin of the coordinate system. Adjust the position of the heating furnace ② so that the axis of the heating furnace coincides with the suspension wire. The samples and crucibles used in the experiment are cleaned with alcohol and blown dry with a hair dryer. Start the cooling water device and observe that the return water is smooth before starting the measurement. Open the balance, reset it, weigh the unloaded mass m1 of the entire suspension system without the sample, apply an excitation current of I=16A, weigh the mass m2 of the unloaded system under the action of the magnetic field, and return the excitation current to zero and the magnetic field to zero. Put the sample into the sample box, weigh the mass m3 of the load system, apply the same excitation current again to measure the mass m4 of the load system under the action of the magnetic field, and return the excitation current to zero and the magnetic field to zero. Take out the sample, turn off the balance, and turn off the cooling water. Substitute the measured value into the following formula:
[0127]
[0128] in, Magnetic field gradient; g: gravitational acceleration; μ0: Bohr magneton.
[0129] 2. Detect conductivity at different temperatures:
[0130] The resistivity (% IACS) of the products obtained in Examples 1 to 3 and Comparative Examples 1 to 3 was tested at 20°C, 40°C, and 80°C according to GB / T 32791-2016 Eddy Current Test Method for Electrical Conductivity of Copper and Copper Alloys.
[0131] project Embodiment 1 Embodiment 2 Embodiment 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[Magnetic susceptibility (×10 -6 )]]> -0.097 -0.095 -0.098 -0.082 0.094 0.085 Electrical conductivity (20℃) 85 87 84 81 83 78 Electrical conductivity (40℃) 75 76 75 71 74 64 Electrical conductivity (80℃) 65 62 64 50 55 44
[0132] 3. The mechanical properties of the products obtained in Experimental Example 3 and Comparative Examples 1-3 were tested, and the results are as follows:
[0133]
[0134]
[0135] The present invention composites the first stainless steel layer, the alloy transition layer, the T2 copper layer, the alloy transition layer and the second stainless steel layer through a cold rolling process to obtain an alloy composite material, thereby avoiding bending deformation caused by the fast heat conduction speed of the thin plate, which affects the accuracy and stability of the final product; in addition, it also avoids the problem of uneven welding and reduced connection strength caused by the difference in melting points of different materials.
[0136] The present invention effectively improves the antimagnetic property and the electrical conductivity by compounding stainless steel and T2 copper, and at the same time improves the corrosion resistance and mechanical strength of the product of the present invention by adding stainless steel; when silicon nitride is not added, the electrical conductivity decreases with the increase of temperature, and is in a linear relationship; by adding a proper amount of silicon nitride, the influence of temperature on the resistivity is significantly reduced, and the weakening of the electrical conductivity caused by the increase of temperature is effectively reduced, especially when the temperature is increased to above 40°C, the influence of temperature change on the electrical conductivity becomes smaller and smaller.
[0137] In summary, the composite technology of the present invention not only achieves a comprehensive improvement in antimagnetic properties, electrical conductivity, corrosion resistance and mechanical strength, but also cleverly solves the performance bottleneck problem of conductive materials at high temperatures by introducing silicon nitride.
[0138] It should be noted that in the above-mentioned experimental examples and comparative examples, the total thickness of the alloy composite material of the circuit board shielding cover is about 0.3 mm (including the first stainless steel layer, the alloy transition layer, the T2 copper layer, the alloy transition layer and the second stainless steel layer), and the thickness of each layer in the experimental examples and comparative examples is compatible with the total thickness of the alloy composite material of the circuit board shielding cover.
[0139] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. The alloy composite material of the circuit board shielding cover is characterized by: It includes a first stainless steel layer, a T2 copper layer and a second stainless steel layer in sequence; Wherein, an alloy transition layer is provided between the first stainless steel layer and the T2 copper layer, and between the second stainless steel layer and the T2 copper layer; The alloy transition layer includes the following components: nickel: 2.2%-2.6%, chromium: 4.5%-5.8%, sulfur ≤0.4%, silicon nitride: 0.2%-0.6%, and the rest is copper and inevitable impurities.
2. The method for preparing the circuit board shielding cover alloy composite material according to claim 1, characterized in that: The following steps are involved: Step 1: weigh raw materials according to the ratio of nickel: 2.2%-2.6%, chromium: 4.5%-5.8%, sulfur ≤0.4%, silicon nitride: 0.2%-0.6%, and the balance is copper, melt the raw materials into a melt, deoxidize the melt in turn, cast it into an ingot, and roll it to obtain an alloy transition layer; Step 2: Compounding the front and back sides of the pickled and roughened T2 copper layer with the alloy transition layer through a cold rolling process to obtain a preliminary composite material; The reduction rate is 4-8%, the rolling force is 7-9MN, and the rolling speed is 2-4m / min; Step 3: Compounding the first stainless steel layer and the second stainless steel layer after pickling and roughening treatment on the front and back sides of the preliminary composite material by cold rolling process, thereby obtaining an alloy composite material of the circuit board shielding cover; The reduction rate is 4-8%, the rolling force is 7-9MN, and the rolling speed is 2-4m / min.
3. The method for preparing the circuit board shielding cover alloy composite material according to claim 2, characterized in that: The thickness of the T2 copper layer is 0.1-0.12 mm.
4. The method for preparing the circuit board shielding cover alloy composite material according to claim 3, characterized in that: The thickness of the first stainless steel layer and the second stainless steel layer is 0.03-0.05 mm.
5. The method for preparing the circuit board shielding cover alloy composite material according to claim 4, characterized in that: The thickness of the transition layer is 0.01-0.05 mm.
6. The method for preparing the circuit board shielding cover alloy composite material according to claim 5, characterized in that: The first stainless steel layer and the second stainless steel layer are made of 304 stainless steel or 316 stainless steel.
7. Use of the alloy composite material of a circuit board shielding cover as claimed in claim 1 in preparing a circuit board shielding cover.
Citation Information
Patent Citations
Circuit board shielding case convenient to replace
CN212573096U